EVALUASI PENGGUNAAN HIJAB PADA MUSLIMAH YANG TIDAK SESUAI DENGAN SYARIAT ISLAM - Risma Cahya Nariti; Niken Amalina Setiyani (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Allah SWT in Islam has emphasized things that are allowed and things that are not allowed, including in covering the aurat both for men and womwn. A good Muslimah is obliged to used closed clothes, one of which is when using the hijab. The use of hijab used by a Muslim woman must be in accordance with Islamic law, so that they avoid all the sins that Allah gives. Therefore, as a good Muslimah and obedient to Allah, she needs to keep her aurat properly and correctly. In the research conducted this time using the library research method where this research uses sources such as books, journals, and scientific works that have a connection with the research topic. The author in this study analyzes, reads, and examines library materials that are in accordance with the problems studied. The aim is to provide a deeper understanding of the use of hijab in accordance with Islamic law and the importance of using hijab for Muslim women